3D laser structuring of supermetalphobic microstructures inside elastomer for multilayer high-density interconnect soft electronics - Chengjun Zhang; Qing Yang; Haoyu Li; Zexiang Luo; Yu Lu; Jialiang Zhang; Cheng Li; Feng Chen (International Journal of Extreme Manufacturing)
High-density interconnect (HDI) soft electronics that can integrate multiple individual functions into one miniaturized monolithic system is promising for applications related to smart healthcare, soft robotics, and human-machine interactions. However, despite the recent advances, the development of three-dimensional (3D) soft electronics with both high resolution and high integration is still challenging because of the lack of efficient manufacturing methods to guarantee interlayer alignment of the high-density vias and reliable interlayer electrical conductivity. Here, an advanced 3D laser printing pathway, based on femtosecond laser direct writing (FLDW), is demonstrated for preparing liquid metal (LM)-based any layer HDI soft electronics. FLDW technology, with the characteristics of high spatial resolution and high precision, allows the maskless fabrication of high-resolution embedded LM microchannels and high-density vertical interconnect accesses for 3D integrated circuits. High-aspect-ratio blind/through LM microstructures are formed inside the elastomer due to the supermetalphobicity induced during laser ablation. The LM-based HDI circuit featuring high resolution (∼1.5 μ m) and high integration (10-layer electrical interconnection) is achieved for customized soft electronics, including various customized multilayer passive electric components, soft multilayer circuit, and cross-scale multimode sensors. The 3D laser printing method provides a versatile approach for developing chip-level soft electronics.